JENIS-JENIS SERANGGA DI SEKITAR PANTAI PERERENAN, MENGWI, KABUPATEN BADUNG - Manik Ermayanti, Ni G. A.; Sudatri, Ni W.; Raka Dalem, A. A. G. (Bumi Lestari Journal of Environment; Vol 7 No 2, 2012)
A Study on insects was carried out on Pererenan, District of Mengwi, Badung Regency, Bali province, between September and December, 2006. Samples were captured using insect nets. The samples were then identified for determination of their species. Their roles on the ecosystem were described. Seven species of butterflies and 29 kinds of other insects were identified on this study. From those, none to be classified as protected species.
Keywords: insects, butterflies, conservation